PEMBERDAYAAN MASYARAKAT DESA LEGETAN KABUPATEN PURWOREJO MELALUI PROGRAM EKOBLOK DARI SAMPAH - Buntara Adi Purwanto; Gunawan Pradasta; Najwa Adawiyyah Polipik; Ahmad Yartadi; Umi Fatmawati; Ahmad Rizky Romadhon; Dendy Maulana (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Plastic waste remains a significant environmental problem in Legetan Village, Bener District, Purworejo Regency. Improper waste management has led to environmental degradation, reduced village aesthetics, and decreased community well-being. These conditions indicate the need for practical and community-based waste management initiatives. This Community Service Program aims to reduce plastic waste volume while enhancing community awareness, knowledge, and active participation in waste management through eco-block innovation. The methods applied include observation, socialization, training, hands-on practice, and community mentoring using a participatory approach. The results indicate positive changes in community attitudes, improved understanding, and increased skills in plastic waste recycling. The community successfully practiced eco-block production as an alternative solution for managing household plastic waste with functional, environmental, and sustainable value.